Taking Container-Based Sanitation to Scale: Opportunities and Challenges - Russel, Kory C.; Hughes, Kelvin; Roach, Mary; Auerbach, David; Foote, Andrew; Kramer, Sasha; Briceño, Raúl (Frontiers in Environmental Science, 2019)
Container-Based Sanitation (CBS) has rapidly progressed from its inception less than a decade ago to its recent classification as a type of improved sanitation facility by the Joint Monitoring Programme. CBS in many ways represents a sustainable service, as it addresses the entire sanitation service chain; offers a variety of service-based business models; and is affordable to people living in marginalized and informal urban settlements. At the same time, CBS services which have been operating for a number of years have grown relatively slowly. Taking CBS to scale will require solving several diverse challenges, particularly the need for government mandates; regulation; and innovative financing. This paper presents the collective views of some of the world’s leading CBS practitioners in an effort to summarize the potential, research gaps, and major challenges to scaling CBS.